Origins of Capitalism and Jewish Ethics : The Thought of Werner Sombart. - Iannuzzi, Ilaria (Cambridge Scholars Publisher, 2022)
This book focuses on the religious origins of the spirit of capitalism through the thought of Werner Sombart. It offers a critical analysis of the link he makes between Jewish ethics and the spirit of capitalism. Sombart's exploration of this topic has not found, to this day, adequate representation in the literature. As such, this book analyses the origins of capitalism through a materialistic and spiritual approach, thus offering an unprecedented methodological and epistemological path.It brings to light a different, little-investigated, avenue of exploration followed by the social processes.
Description based upon print version of record.
Keywords: Capitalism -- History.; Capitalism -- Religious aspects -- Judaism.; Jewish ethics.; Morale juive.; Capitalism; Capitalism -- Religious aspects -- Judaism; Jewish ethics; History